2001
DOI: 10.1097/00000658-200101000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Trial of Sentinel Node Biopsy for Breast Cancer Using Both Technetium Sulfur Colloid and Isosulfan Blue Dye

Abstract: ObjectiveTo determine the factors associated with false-negative results on sentinel node biopsy and sentinel node localization (identification rate) in patients with breast cancer enrolled in a multicenter trial using a combination technique of isosulfan blue with technetium sulfur colloid (Tc99). Summary Background DataSentinel node biopsy is a diagnostic test used to detect breast cancer metastases. To test the reliability of this method, a complete lymph node dissection must be performed to determine the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
160
4
9

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(200 citation statements)
references
References 19 publications
27
160
4
9
Order By: Relevance
“…The detection rate of 98% for the SLN in 43 patients was comparable to that of the standard technique using a combination of radioisotope scanning and blue dye staining. Detection rate (97.7%), sensitivity (94.4%), and falsenegative rate (5.6%) in this study were also similar to that reported for the combined method with a detection rate approximating 95% [3,28].…”
Section: Discussionsupporting
confidence: 87%
“…The detection rate of 98% for the SLN in 43 patients was comparable to that of the standard technique using a combination of radioisotope scanning and blue dye staining. Detection rate (97.7%), sensitivity (94.4%), and falsenegative rate (5.6%) in this study were also similar to that reported for the combined method with a detection rate approximating 95% [3,28].…”
Section: Discussionsupporting
confidence: 87%
“…Complete fi nal results of two large randomized trials (NSABP B-32, ALMANAC) are awaited in this regard [78,79]. Outside clinical trials, patients who are found to have a positive sentinel lymph node by H and E should undergo a completion axillary dissection, since a number of studies have shown that nonsentinel nodes can also be involved in 30-50% of cases [59,71,80].…”
Section: Discussionmentioning
confidence: 99%
“…at least 90% sentinel lymph node detection rate and less than 5% false-negative rate indicates that only sentinel lymph node biopsy without axillary dissection can be made. Tafra et al (21) reported that 30 cases are adequate for the learning phase. In the ALMANAC study, it has been reported that at least 40 patients are required (22).…”
Section: Discussionmentioning
confidence: 99%